Stable and ordered amide frameworks synthesised under reversible conditions which facilitate error checking - Stewart, David (Nat Commun, 2017)
Covalent organic frameworks (COFs) are network polymers with long-range positional order whose properties can be tuned using the isoreticular chemistry approach. Making COFs from strong bonds is challenging because irreversible rapid formation of the network produces amorphous materials with locked-in disorder. Reversibility in bond formation is essential to generate ordered networks, as it allows the error-checking that permits the network to crystallise, and so candidate network-forming chemistries such as amide that are irreversible under conventional low temperature bond-forming conditions have been underexplored. Here we show that we can prepare two- and three-dimensional covalent amide frameworks (CAFs) by devitrification of amorphous polyamide network polymers using high-temperature and high-pressure reaction conditions. In this way we have accessed reversible amide bond formation that allows crystalline order to develop. This strategy permits the direct synthesis of practically irreversible ordered amide networks that are stable thermally and under both strong acidic and basic hydrolytic conditions.